Development of Demonstration-Based Tutorial Video Media to Improve Restaurant Employees' Product Knowledge Competence - Putu Darma Wisada; Harun Sitompul; Dewi Endriani (CV. Media Inti Teknologi, 2026)
Background: The fierce competition in the restaurant industry demands excellent product knowledge mastery to ensure customer satisfaction. However, training evaluation data reveals a gap between formal training and actual performance, which is reinforced by customer complaints regarding product delivery errors.Aims: This study aims to develop demonstration-based tutorial video media to improve the product knowledge competence of restaurant employees.Methods: This research applies the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with a One Group Pretest-Posttest design involving 40 employees. Data were collected through feasibility questionnaires (validated by 2 material experts, 2 instructional design experts, and 2 media experts), employee practicality questionnaires, and multiple-choice tests (pre-test and post-test) to measure effectiveness using the N-Gain score. Data analysis utilized quantitative and qualitative descriptive methods.Results: Validation tests showed highly valid results: 98.33% for material, 97.50% for instructional design, and 89.41% for media. The practicality test reached 90.41% (highly practical). In the effectiveness test, the average score increased from 55.33% (moderately effective) in the pre-test to 81.00% (highly effective) in the post-test. The N-Gain calculation yielded a score of 0.51, indicating a moderate improvement category.Conclusion: Overall, the demonstration-based tutorial video media is proven valid, practical, and effective in improving the product knowledge competence of restaurant employees.